Heterogeneity of Genetic Landscapes in Salivary Gland Tumors and Their Critical Roles in Current Management - Anam YOUSAF; Sarina SULONG; Baharudin ABDULLAH; Norhafiza Mat LAZIM (Medeniyet Medical Journal)
Salivary gland neoplasms (SGNs) are rare and heterogeneous tumors in the head and neck region. Although progress has been recently made in revealing the molecular landscape of salivary glands tumors, it is limited and appears to be the tip of the iceberg. Some genetic aberrations include chromosomal translocations, such as CRTC1/3-MAML2 in mucoepidermoid carcinoma, g MYB-NFIB gene fusions in adenoid cystic carcinoma, and PLAG1-HMGA2 gene changes in pleomorphic adenoma and carcinoma ex pleomorphic adenoma. These chromosomal translocations provide fresh insights into the molecular etiology of diverse SGNs and aid in their classification and in approaching treatment. In future, these genetic variations may serve as critical tools for diagnosing salivary gland tumors and optimizing the management as well as prognosis of patients. This review presents the most recent advances in the molecular pathology of salivary gland cancers, with an emphasis on distinguishing molecular features that can be used for optimizing current patient management.